Incidence, Severity and Prognosis Associated with Hyponatremia in Dogs and Cats. (13th May 2015) - Ueda, Y.; Hopper, K.; Epstein, S.E.
<x xml:space="preserve">Abstract</x> Background Hyponatremia is a common electrolyte abnormality in human patients and is associated with substantial morbidity and death. The incidence and importance of hyponatremia in dogs and cats has not been determined. Hypothesis/Objectives To describe the incidence of and prognosis associated with hyponatremia in dogs and cats at a university teaching hospital. Animals Of 16, 691 dogs and 4, 211 cats with measured blood or serum sodium concentration. Methods Retrospective study. Medical records of animals with a blood or serum sodium concentration measured during a 60‐month period were reviewed to determine the severity of hyponatremia and its associated fatality rate. Cases with moderate (11–15 mmol/L below the reference range) or severe hyponatremia (≥16 mmol/L below the reference range) were further reviewed. Results Of 4, 254 dogs (25.5%) and 2, 081 cats (49.4%) were diagnosed with hyponatremia. Case fatality rates of dogs and cats with hyponatremia were 13.7% and 11.9%, respectively, compared to 4.4% and 4.5% with a normal blood or serum sodium concentration (P < 0.0001). The magnitude of hyponatremia was linearly associated with a higher case fatality rate (P < 0.0001). Hyponatremia was associated with a lower case fatality rate than hypernatremia in the same population. Among the animals with moderate or severe hyponatremia, 92.1% of dogs and 90.6% of cats presented with community‐acquired hyponatremia, and 7.9% of dogs and 9.4% of cats developed hospital‐acquired hyponatremia. Conclusions and clinical importance Hyponatremia was found commonly in this population and was associated with increased case fatality rate. Presence and severity of hyponatremia might be useful as a prognostic indicator.